Abnormal Returns Before and After the January Effect - Yana Fajriah; Edy Jumady; Syamsul Alam (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This research aims to see if there is a difference in LQ45 share abnormal returns before and after the January effect. The non-probability sampling method was used in this study, and data from 45 companies were obtained using this method. In this study, secondary data from financial reports obtained from yahoo.finance.com was used as the source of data. The Event Study technique was used in this study, with the Event Window consisting of seven days before and seven days after the January Effect event. The research data was put to the test using a normality test and a paired sample test to test the hypothesis. The results revealed that the Abnormal Return on LQ45 companies listed on the Indonesia Stock Exchange did not differ significantly before and after the January Effect. One of the references used by the entity's stakeholders in making decisions is managerial interest in window dressing.